Sirtuin 2 Alleviates Chronic Neuropathic Pain by Suppressing Ferroptosis in Rats - Zhang, Xiaojiao; Song, Tao; Zhao, Mengnan; Tao, Xueshu; Zhang, Bohan; Sun, Cong; Wang, Pinying; Wang, Kunpeng; Zhao, Lin (Frontiers in Pharmacology, 2022)
Neuropathic pain (NP) is chronic and associated with poor effects of general analgesia. It affects patients’ health and quality of life. The apoptotic process of lipid peroxidation caused by iron overload is called ferroptosis, which may be associated with nervous system disease. A recent study has found that sirtuin 2 (SIRT2) achieves a neuroprotective effect by suppressing ferroptosis. Herein, we aimed to examine whether SIRT2 regulated spared nerve injury (SNI)-induced NP by suppressing ferroptosis in rats. A rat model of NP was induced in adult male Sprague-Dawley rats weighing 200–250 g. Mechanical allodynia was observed from the first day after SNI and continued for 14 days. Compared with age-matched control rats, the expression of SIRT2 and ferroportin 1 (FPN1) decreased in the L4-6 spinal cord of the SNI-induced NP rats. In addition, we observed that the levels of both iron and anti-acyl-coenzyme A synthetase long-chain family member 4 (ACSL4) were significantly increased in the spinal cord after SNI, while the expression of glutathione peroxidase 4 (GPX4) was decreased. Furthermore, an intrathecal injection of SIRT2 overexpressed recombinant adenovirus, which upregulated the expression of SIRT2, attenuated mechanical allodynia, enhanced the level of FPN1, inhibited intracellular iron accumulation, and reduced oxidant stress levels, thereby reversing the changes to ACSL4 and GPX4 expression in the SNI rats. This evidence suggests that SIRT2-targeted therapeutics may help relieve the symptoms of chronic NP.